Pengaruh Marked Value Added (MVA), Price Book Value (PBV), dan Total Asset Turnover (TATO) Terhadap Harga Saham Pada Perusahaan Subsektor Telekomunikasi Yang Terdaftar di BEI - Sabita, Bulqis; Nurulrahmatiah, Nafisah; Juwani, Juwani (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of Market Value Added (MVA), Price Book Value (PBV), and Total Asset Turnover (TATO) on stock prices of telecommunication subsector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The research employed a quantitative approach using multiple linear regression analysis. The sample consisted of three companies, PT Telkom Indonesia Tbk, PT Indosat Tbk, and PT XL Axiata Tbk, selected through purposive sampling. The results show that MVA and PBV have a significant positive effect on stock prices, while TATO has no significant effect. Simultaneously, MVA, PBV, and TATO significantly influence stock prices with a determination coefficient of 68.3%. These findings indicate that investors place greater emphasis on value-added and market perception indicators rather than asset efficiency in making investment decisions within the telecommunication subsector. This study provides practical implications for company management to enhance value creation through innovation and strategic asset management, as well as academic contributions to enrich the literature on stock price determinants in the Indonesian capital market.